Endodontic treatment of destructive chronic apical periodontitis after apicectomy in the medical history (Эндодонтия Today, 2020)
The article describes the methods of repeated endodontic treatment of destructive chronic apical periodontitis after apicectomy. 20 patients aged 25 - 35 years with a diagnosis of chronic apical destructive periodontitis were treated. All patients had a history of surgical apicectomy. A clinical example proves the efficiency of the proposed technique. The drug of «Bioimplant» together with the gel of «Collapan» were used in the treatment.